2017
DOI: 10.1177/1948550617727588
|View full text |Cite
|
Sign up to set email alerts
|

Benevolent Sexism and Hostile Sexism Across the Ages

Abstract: Ambivalent sexism theory states that prejudice toward women comprises two interrelated ideologies. Endorsement of hostile sexism—aggressive and competitive attitudes toward women—is linked with endorsement of benevolent sexism—paternalistic and patronizing attitudes toward women. We conduct the first systematic tests of how endorsement of sexism differs across age and across time, using six waves of a nationally representative panel sample of New Zealand adults ( N = 10,398). Results indicated U-shaped traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 34 publications
5
61
1
5
Order By: Relevance
“…Finally, some research shows an agreement U-shaped pattern with these IPVAW supportive attitudes, with the highest levels of agreement at the beginning and at the end of the age range, and the lowest in the middle [33]. This type of curvilinear relationship has also been observed in some studies on sexist beliefs, with high levels of sexism among young people, lower levels in adulthood and again high levels in older people [34][35][36]. A possible explanation for these results could be that "the feminist movement of the 1960s changed attitudes in young people at that time, who are now middle-aged, and those gains have receded as the movement has become less salient and backlash has set in" [34] (p. 74).…”
Section: Introductionmentioning
confidence: 52%
“…Finally, some research shows an agreement U-shaped pattern with these IPVAW supportive attitudes, with the highest levels of agreement at the beginning and at the end of the age range, and the lowest in the middle [33]. This type of curvilinear relationship has also been observed in some studies on sexist beliefs, with high levels of sexism among young people, lower levels in adulthood and again high levels in older people [34][35][36]. A possible explanation for these results could be that "the feminist movement of the 1960s changed attitudes in young people at that time, who are now middle-aged, and those gains have receded as the movement has become less salient and backlash has set in" [34] (p. 74).…”
Section: Introductionmentioning
confidence: 52%
“…Thus, future research should consider how women's relationship insecurity promotes hostility toward other women, in particular attitudes about women being sexually manipulative and untrustworthy.A recurring theme across this review is that romantic relationships can foster people's endorsement or rejection of sexism. However, an unresolved proposition of ambivalent sexism theory and our research is that formative experiences within heterosexual romantic relationships should be similarly formative for the development of sexist attitudes(Glick & Hilt, 2000;Hammond, Milojev, Huang, & Sibley, 2018). Evidence for this proposition is inconsistent:prior research has found that adolescent boys' experience with romantic relationships is associated with greater benevolent sexism(Montañés, Megías, de Lemus, & Moya, 2015), or greater hostile sexism (de Lemus,Moya, & Glick,…”
mentioning
confidence: 71%
“…A recurring theme across this review is that romantic relationships can foster people's endorsement or rejection of sexism. However, an unresolved proposition of ambivalent sexism theory and our research is that formative experiences within heterosexual romantic relationships should be similarly formative for the development of sexist attitudes (Glick & Hilt, ; Hammond, Milojev, Huang, & Sibley, ). Evidence for this proposition is inconsistent: prior research has found that adolescent boys' experience with romantic relationships is associated with greater benevolent sexism (Montañés, Megías, de Lemus, & Moya, ), or greater hostile sexism (de Lemus, Moya, & Glick, ; Viejo, Ortega‐Ruiz, & Sánchez, ), or neither (Mastari, Spruyt, & Siongers, ; for a review, see Ramiro‐Sánchez, Ramiro, Bermúdez, & Buela‐Casal, ).…”
Section: Theoretical Advancements and Future Directionsmentioning
confidence: 86%
“…Second, we made the theoretical assumption that people’s endorsement of hostile sexism is relatively stable across time and causally influences their perceptions of women (Glick et al, 1997; Hammond et al, 2018). However, the correlational nature of the data prevents concluding that hostile sexism causes biased perceptions.…”
Section: Discussionmentioning
confidence: 99%